Artificial intelligence for the defence of Japan: cautious but steady progress - Tomida, Haruka (2025)
The Japan Ministry of Defense announced the basic policy for the promotion of AI utilisation for the first time on 2 July 2024. Although the ministry has already promoted various AI-related initiatives, the new policy will accelerate existing initiatives and create momentum.